1963
DOI: 10.1063/1.1734361
|View full text |Cite
|
Sign up to set email alerts
|

Chemiluminescent Reactions Involving Atomic Oxygen and Nitrogen

Abstract: The emission excited in the association of atomic oxygen and nitrogen has been studied in a fast-flow low-pressure system by photoelectric and spectroscopic methods. The absolute rates of excitation of the products of these associative processes have been measured, and the effects of added quenching gases have been investigated. Specific excitation processes consistent with the present observations are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
56
0

Year Published

1965
1965
1985
1985

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 160 publications
(57 citation statements)
references
References 48 publications
1
56
0
Order By: Relevance
“…Three subsequent laboratory studies (16)(17)(18) have reported values for the composite emission rate constant, k,, in the expression A fourth study (19) reported absolute rate constants for reactions with 0 ( 3 P ) , O,, and Ar. Subsequent work in this laboratory has refined these rate constants as well as extending the list of quenchers investigated.…”
mentioning
confidence: 99%
“…Three subsequent laboratory studies (16)(17)(18) have reported values for the composite emission rate constant, k,, in the expression A fourth study (19) reported absolute rate constants for reactions with 0 ( 3 P ) , O,, and Ar. Subsequent work in this laboratory has refined these rate constants as well as extending the list of quenchers investigated.…”
mentioning
confidence: 99%
“…+ ko' where ko and kO1 represent a unimolecular loss of N and N2* then the exponentials in eqs. [6] and [7] become similarly modified. The observed values of ko from Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Thus using the data in Phillips (4) earlier paper (with 1121 increased by 4 (I)), assuming [N2*]0 is negligible, setting the first derivative of eq. [7] with respect to time to zero, and substituting y = 21c1/kz, one finds the condition for a inaxiinuill to be y = exp -kz(l -y)[I2]t for y # 1.…”
Section: Discussionmentioning
confidence: 99%
“…However, a second 0-green line intensity maximum is observed near 180 km to which the reaction 02+ + e-. OVS) + O('P) (36) contributes in a ma.iuv way. Reaction (0) is 2.8 eV exothermici since the only products are atomic spec,,.…”
Section: B Natural Choma Ltminescence (Airalow)mentioning
confidence: 98%